2017
DOI: 10.1136/bmjdrc-2017-000420
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose-lowering effect of whey protein depends upon clinical characteristics of patients with type 2 diabetes

Abstract: ObjectiveWhey protein (WP) intake has been shown to reduce postprandial glycemia. Majority of WP research in type 2 diabetes (T2DM) involved acute challenge or weight loss studies. It is not known if WP supplementation can provide sustained glucose lowering. Our goal was to investigate the effects of WP on glycemia comprehensively by using continuous glucose monitoring (CGM) while avoiding the confounding effects of variable food intake through controlled feeding.Research design and methodsThis double-blinded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Incretin and insulin responses to protein are established. 26 Nonetheless, excluding a single study by Lindgren et al, 5 the effect of AA on incretin hormones release remains poorly defined. Moreover, this previous study employed AA mixtures, containing both essential and non-essential AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incretin and insulin responses to protein are established. 26 Nonetheless, excluding a single study by Lindgren et al, 5 the effect of AA on incretin hormones release remains poorly defined. Moreover, this previous study employed AA mixtures, containing both essential and non-essential AA.…”
Section: Discussionmentioning
confidence: 99%
“…EAA, essential amino acids; GIP, glucose-dependent insulinotropic peptide; GLP-1, glucagon-like peptide-1 have demonstrated that this effect of incretin hormone production (at least in response to EAA) does not appear to be affected by the process of physiological ageing.Incretin and insulin responses to protein are established 26. Finally, our studies F I G U R E 3 Oral vs IV EAA.…”
mentioning
confidence: 81%
“…While postprandial insulin secretion in response to glucose intake is blunted in patients with T2DM, other noncarbohydrate nutrients, such as proteins, have been found to be useful for stimulating insulin secretion in T2DM patients . In this case, there is ample evidence that milk proteins increase the postprandial insulin response and lower the postprandial blood glucose response in both healthy subjects and patients with T2DM . It has been suggested that postprandial glucose levels are important predictors for overall glucose control, particularly in T2DM patients with mild or moderate hemoglobin A1c (HbA1c) .…”
Section: The Rationale For Milk Protein Supplementation In the Prevenmentioning
confidence: 99%
“…Several trials in healthy subjects and patients with T2DM have indicated that whey significantly increases the postprandial GIP response to a greater extent than casein and other types of protein. On the other hand, the effects of milk proteins on GLP‐1 are equivocal, but several studies showed that whey triggered the strongest GLP‐1 response in healthy subjects compared with that triggered by casein or soy . The findings of a long‐term trial in 48 patients with T2DM showed that the consumption of a whey protein‐based breakfast resulted in the lowest overall area under the curve for postprandial plasma glucose, ghrelin, and hunger and the highest overall area under the curve for postprandial plasma insulin, C‐peptide, GLP‐1, and satiety scores compared with a mixed protein breakfast or carbohydrate‐based breakfast.…”
Section: The Rationale For Milk Protein Supplementation In the Prevenmentioning
confidence: 99%
See 1 more Smart Citation